Structure of Transmembrane Helix 8 and Possible Membrane Defects in CFTR - Corradi, Valentina (Biophys J, 2018)
The cystic fibrosis transmembrane conductance regulator (CFTR) is an ion channel that regulates the flow of anions across epithelia. Mutations in CFTR cause cystic fibrosis. CFTR belongs to the ATP-binding cassette transporter superfamily, and gating is controlled by phosphorylation and ATP binding and hydrolysis. Recently obtained ATP-free and ATP-bound structures of zebrafish CFTR revealed an unwound segment of transmembrane helix (TM) 8, which appears to be a unique feature of CFTR not present in other ATP-binding cassette transporter structures. Here, using μs-long molecular dynamics simulations, we investigate the interactions formed by this TM8 segment with nearby helices in both ATP-free and ATP-bound states. We highlight ATP-dependent interactions as well as the structural role of TM8 in maintaining the functional architecture of the pore via interactions common to both the ATP-bound and ATP-free state. The results of the molecular dynamics simulations are discussed in the context of the gating mechanism of CFTR.